Statistical energy analysis: a brief introduction - Davies, H.G. (Canadian Acoustics, 1982)
Statistical energy analysis (SEA) in a powerful tool in the study of high frequency vibration. A brief review is given of the basic ideas of SEA by describing some sample calculations and listing some areas where SEA has been applied successfully